Ice cream consumption in a selected area of Bangladesh: Effect of demographic, psychometric and product factors - Begum, Aysha; Palash, M Salauddin; Alam, Md Akhtarul; Begum, Maimuna (Journal of the Bangladesh Agricultural University, 2020)
Ice cream is an emerging sector in today’s business world. This paper aims to explore the most significant demographic, psychometric and product factors and their strength of relationship with households’ ice cream consumption. Based on a field survey of 120 consumers, descriptive statistics and regression analysis were performed to achieve the desired goals. This study revealed four demographic factors, four product features and two psychometric factors that were the most influential to ice cream consumption. Consumers’ gender, family type, monthly food expenditure and food buying decision maker were found to be influential factors of purchasing ice cream. Female consumers were more likely to consume more ice cream than their male counterparts. Similarly, the female decision maker was likely to purchase more ice cream than the male decision maker. The most influential psychometric motive of ice cream consumption was consuming a tasty dessert and not delivering calories. In addition, ice cream price, brand loyalty, packaging attractiveness and taste were the substantial product factors behind consumption. This work adds value to the literature by expanding our knowledge on consumers’ ice cream consumption and it also provides important product feature related information for the marketers that drive consumer ice cream preference. J Bangladesh Agril Univ 18(1): 165–171, 2020 https://doi.org/10.5455/JBAU.94757